Simplified medicine: a guide to writing clear and accessible articles for the general public - Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association (MIMPA), 2024)
As medical professionals, we are entrusted not only with treating patients but also with disseminating accurate health information to the wider community. However, bridging the gap between complex medical concepts and the public’s understanding can often be a daunting task. This book aims to empower healthcare professionals with the knowledge and skills necessary to communicate effectively with diverse audiences. Whether you’re a seasoned healthcare professional or a novice writer, this book is designed to support you on your journey towards becoming a more confident and proficient medical communicator.